2018
DOI: 10.1097/dss.0000000000001445
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a High-Resolution Superficial Diagnostic Ultrasound System for Assessing Skin Thickness: A Cross-Sectional Study

Abstract: This is the first study using high-resolution superficial diagnostic ultrasound to map skin thickness of the face and neck at standard anatomic locations. Ultrasound is an inexpensive, noninvasive, and convenient means to monitor dermatologic conditions and guide their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
0
22
1
Order By: Relevance
“…Several diagnostic imaging devices methodologies such as computed tomography, magnetic resonance imaging, and ultrasonography (US) have been commonly used to investigate the skin and the subcutaneous fat layer (Foissac et al, ; Gosain et al, ; Gülbitti et al, ; Iyengar et al, ; Schenck et al, ; Wysong et al, ). Due to technical limitation such as a localized low imaging resolution, previous studies could not demonstrate the topography of the skin and superficial fat thicknesses over the entire face.…”
Section: Introductionmentioning
confidence: 99%
“…Several diagnostic imaging devices methodologies such as computed tomography, magnetic resonance imaging, and ultrasonography (US) have been commonly used to investigate the skin and the subcutaneous fat layer (Foissac et al, ; Gosain et al, ; Gülbitti et al, ; Iyengar et al, ; Schenck et al, ; Wysong et al, ). Due to technical limitation such as a localized low imaging resolution, previous studies could not demonstrate the topography of the skin and superficial fat thicknesses over the entire face.…”
Section: Introductionmentioning
confidence: 99%
“…As the technology has improved, so has its utility. In an early study of over 4300 skin lesions, Wortsman et al demonstrated the ability of higher frequency ultrasound (7)(8)(9)(10)(11)(12)(13)(14)(15) to significantly improve diagnostic accuracy. Compared to clinical examination alone, ultrasound corrected the referring diagnosis in 17% of cases and detected 3 missed malignancies [9].…”
Section: History Of Ultrasound In Medicinementioning
confidence: 99%
“…Many devices include color Doppler analysis for characterization of blood flow and vessel morphology. It is readily available and can be easily incorporated into clinical practice [10,11,15].…”
Section: Ultrasound Technology and How It Workmentioning
confidence: 99%
See 2 more Smart Citations